Strategy to Overcome the Constraints of Drip Irrigation System : A Study of Panchayat Samiti, Jhotwara, District Jaipur (Rajasthan) - Yadav, Krishna; Yadav, J.P.; Kumawat, Pushpa; Yadav, Seema (Indian Journal of Extension Education, 2019)
The Indian population is continuously increasing which demand more food grain production to fill vagaries of population. Therefore, to meet the projected food demands of 21st century and to harvest maximum benefits from every unit of available land, resource and other critical inputs needs to be exploited. Water is the most precious natural source, vitally important for agricultural development and day-to-day living of human beings. In the changing agricultural scenario world over and shift towards precision farming, drip irrigation happens to be the technology capable of providing more efficient utilization of water. The study was conducted in Jhotwara panchayat samiti of district Jaipur (Rajasthan). Fifty per cent (8) Gram Panchayats where maximum number of drip irrigation sets installed were selected. Two villages from each selected Gram Panchayats were selected randomly. Ninety six farmers were selected from sixteen selected village by using of random sampling technique through proportional allocation to be size of sample. The study shows that the among the important suggestions offered by the drip irrigation adopters to overcome the constraints faced in adoption of recommended improved practices of drip irrigation system, “Provision of sufficient subsidy to reduce initial installation cost” (91.66%) which was prioritized at top level. Least priority was given to the appropriate strategy i.e. “Control on nepotism and favoritism in installation of drip sets on subsidized rate” (55.20%).
Keywords: Constraints; Drip irrigation system